A Stacked Patch Antenna With Broadband Circular Polarization and Flat Gains - Kang Ding (IEEE Access, 2021)
In this paper, a stacked circular polarization (CP) patch antenna with broad impedance bandwidth, axial-ratio (AR) bandwidth, and flat gains is investigated. The antenna is composed of a square ring, double layers' stacked patches, and four vertical patches. The corner truncated loop served as a sequential phase feeding structure for four driven patches. To improve the impedance matching, four square patches are stacked on the bottom layer. Furthermore, four vertical patches are introduced on the ground plane to broaden the AR bandwidth. Simulated and measured studies are conducted on an antenna prototype to validate the proposed design. The proposed design shows that the measured impedance bandwidth is 4.65-7.21 GHz (43.2%), measured 3-dB AR bandwidth at broadside is 4.9-6.4 GHz (26.5%) and the 1-dB gain bandwidth is 4.75-6.6 GHz (32.6%). Compared with other similar CP stacked patch antennas, the antenna owns advantages of wide bandwidth, compact size, and flat gain.